Conflict, Territory and the Frontier Economy: Smuggling in the Alps of Dauphiné During the 18th Century - Anne Montenach (Revue de Géographie Alpine)
This article takes up the theme of “mountains and conflict” with a review of smuggling in the Dauphiné Alps during the 18th century. As a “foreign” and border province, smuggling was rife in Dauphiné and practised by a variety of inhabitants. For some, it was part of the daily strategy for survival, for others their normal commercial practice, while for states it became a bargaining chip in negotiations over trade wars. Paradoxically, the frontier was not only a barrier but also a passage, depending on the different scenarios enacted along its length: a resource, a porous fence, a key place for affirming state power, and an opportunity to circumvent state authority. At a time when nation-states were seeking to affirm their presence, the frontier between Dauphiné and Piedmont, and more specifically the border defining the privileges granted to the Briançon and Queyras districts, offers an excellent opportunity for studying the territorial, economic and social situations generated by the very presence of frontiers and the various forms of power relationships involved in or controlling illegal commerce. This article reviews the conditions surrounding the emergence of a black market in two products, the one heavily taxed (salt) and the other banned (calicos), both of which were in high demand by European consumers during the 17th and 18th centuries.